2017
DOI: 10.1111/imm.12787
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐11 non‐canonical inflammasome: a critical sensor of intracellular lipopolysaccharide in macrophage‐mediated inflammatory responses

Abstract: SummaryInflammatory responses mediated by macrophages are part of the innate immune system, whose role is to protect against invading pathogens. Lipopolysaccharide (LPS) found in the outer membrane of Gram-negative bacteria stimulates an inflammatory response by macrophages. During the inflammatory response, extracellular LPS is recognized by Toll-like receptor 4, one of the pattern recognition receptors that activates inflammatory signalling pathways and leads to the production of inflammatory mediators. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
219
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(221 citation statements)
references
References 89 publications
(264 reference statements)
2
219
0
Order By: Relevance
“…For example, Nakamura et al demonstrated that the NOD2 ligand muramyl dipeptide is transported from endosomes into the cytosol through endosomal membrane peptide transporters, solute carrier (SLC)15A3, and SLC15A4 in dendritic cells and macrophages. In addition, recent studies reported that LPS is released from Gram‐negative bacterium‐containing vacuoles into the cytosol by guanylate‐binding protein‐mediated lysis of the vacuoles and then directly binds to pro‐caspase‐11, leading to non‐canonical inflammasome activation in macrophages . The cytosolic entry mechanisms of microbial components, such as muramyl dipeptide and LPS, might be involved in those of lipoproteins and lipopeptides.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nakamura et al demonstrated that the NOD2 ligand muramyl dipeptide is transported from endosomes into the cytosol through endosomal membrane peptide transporters, solute carrier (SLC)15A3, and SLC15A4 in dendritic cells and macrophages. In addition, recent studies reported that LPS is released from Gram‐negative bacterium‐containing vacuoles into the cytosol by guanylate‐binding protein‐mediated lysis of the vacuoles and then directly binds to pro‐caspase‐11, leading to non‐canonical inflammasome activation in macrophages . The cytosolic entry mechanisms of microbial components, such as muramyl dipeptide and LPS, might be involved in those of lipoproteins and lipopeptides.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular PRRs induce inflammatory responses in a unique way by forming “inflammasomes,” intracellular protein complexes containing PRRs and inflammatory molecules . NLRs (e.g., NLRP1, NLRP3, and NLRC4) and AIM2 are activated by different stimuli and assemble “canonical inflammasomes” consisting of PRRs and pro‐caspase‐1 with or without the ASC.…”
Section: Inflammasomes: Structures and Activationmentioning
confidence: 99%
“…Caspase‐11 inflammasome is activated by directly interacting with intracellular LPS of Escherichia coli , Legionella pneumophilia , Salmonella typhimurium , Shigella flexneri , Citrobacter rodentium , and Burkholderia spp. Caspase‐11 inflammasome assembles by direct interaction between caspase‐11 CARD and LPS lipid A moiety (Figure E), allowing oligomerization of caspase‐11‐LPS (Figure F) . Caspase‐11 was initially discovered in mice, and recent studies identified caspase‐4 and ‐5 as human homologs of mouse caspase‐11 due to their ability to interact directly with intracellular LPS and to activate inflammasome pathways .…”
Section: Inflammasomes: Structures and Activationmentioning
confidence: 99%
See 2 more Smart Citations